2017
DOI: 10.1080/10826084.2017.1306564
|View full text |Cite
|
Sign up to set email alerts
|

Report on the International Workshop on Drug Prevention and Treatment in Rural Settings Organized by United Nation Office on Drugs and Crime (UNODC) and World Health Organization (WHO)

Abstract: Very little evidence has been reported in literature regarding the misuse of substances in rural areas. Despite the common perception of rural communities as a protective and risk-mitigating environment, the scientific literature demonstrated the existence of many risk factors in rural communities. The Drug Prevention and Health Branch (DHB) of the United Nations Office on Drugs and Crime (UNODC), and the World Health Organization (WHO), in June 2016, organized a meeting of experts in treatment and prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Some authors report that rural populations have less social risk factors and deprivations than urban inhabitants,36 which could in part explain the particularly low prevalence of DD in our study. Furthermore, in remote and isolated areas there is a high rate of stigmatization,3739 which may interfere with access to all treatment services and treatment seeking behaviours related to SUD,29,37 so that our data could underestimate the real extent of DD prevalence.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some authors report that rural populations have less social risk factors and deprivations than urban inhabitants,36 which could in part explain the particularly low prevalence of DD in our study. Furthermore, in remote and isolated areas there is a high rate of stigmatization,3739 which may interfere with access to all treatment services and treatment seeking behaviours related to SUD,29,37 so that our data could underestimate the real extent of DD prevalence.…”
Section: Discussionmentioning
confidence: 94%
“…Common perception is that in comparison to urban settings, rural communities are a safer environment in regards of SUD,29 nevertheless some authors reported that rural status confers several general disadvantages, such as less perceived risk, reduced exposure to prevention messages and specific disadvantages for health-care use measures, regardless of poverty and health-care supply 30,31. Besides, Chasnoff and colleagues reported that rural children are more likely to have mental health challenges, such as internalizing behaviours and anxiety or mood disorders, than urban children 32…”
Section: Introductionmentioning
confidence: 99%
“…Brief, personalized, and interactive interventions delivered via computer or online show promise in the prevention of substance use among secondary school students in remote and under-resourced settings (Milano et al, 2017; UNODC, 2017), and this pilot study showed that the multimedia family-focused intervention for at-risk youth is feasible and acceptable in the context of a middle-income country affected by a drug epidemic. Despite initial hesitance from community board members about the intervention’s ability to engage and retain parents of at-risk youth, every family in the study except one attended all pilot sessions and were eager to receive additional information.…”
Section: Discussionmentioning
confidence: 97%
“…A number of strategies have been reported to reduce substance abuse among rural youth, including warding off the "boredom of the countryside" (Ceccato 2015b). In general, measures that include interactive elements and community-based efforts have had shown better outcomes (Milano et al 2017;Stallwitz 2016).…”
Section: Prevention Of Some Typical Rural Issuesmentioning
confidence: 99%